2000
DOI: 10.1046/j.1440-1622.2000.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience With the Holmium Laser as an Endoscopic Lithotrite

Abstract: Ureteric stone position can limit the use of extracorporeal shock wave lithotripsy due to imaging difficulties. Ureteric lithotripsy overcomes this problem. The holmium laser has proven to be safe and effective in clearing urinary stone burdens of a variety of sizes, sites and compositions in this cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
1
9
0
2
Order By: Relevance
“…The results of holmium laser lithotripsy for ureteral calculi have been uniformly excellent [11,[14][15][16][17][18][19]. Successful fragmentation of calculi is achieved in more than 85% cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of holmium laser lithotripsy for ureteral calculi have been uniformly excellent [11,[14][15][16][17][18][19]. Successful fragmentation of calculi is achieved in more than 85% cases.…”
Section: Resultsmentioning
confidence: 99%
“…The final determinant of success is not the laser itself but other factors such as stone location, stone size and difficulty of access because of associated anatomical abnormalities or ureteral narrowing [20]. Recent work of Costello et al [18], has shown 100% success rate. The holmium laser essentially will fragment all calculi regardless of colour and composition including cystine, calcium oxalate monohydrate and brushite [21].…”
Section: Resultsmentioning
confidence: 99%
“…With the use of thinner instruments, a skilled urologist can approach ureteral calculi in a quicker and more cost-effective manner than SWL [3][4][5][6][7][8][9][10][11][12][13] . Adequate and immediate decompression of the obstruction constitutes the major advantage of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although very low complication rates were noted especially in distal and middle ureteral calculi, a relatively higher complication rate was noted in the management of proximally located stones. Different intracorporeal lithotriptors can be used with certain advantages and disadvantages and with varying degrees of success [10][11][12][13] . Although laser application in the disintegration of the ureteral calculi has changed the treatment concepts to a meaningful extent, studies have shown that pneumatic intracorporeal lithotripsy is also well tolerated and is a cost-effective alternative that achieves stone-free rates of up to 85% [18][19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation